Apical Accumulation of the Sevenless Receptor Tyrosine Kinase During Drosophila Eye Development Is Promoted by the Small GTPase Rap1. Issue 4 (1st August 2014) - Baril, Caroline; Lefrançois, Martin; Sahmi, Malha; Knævelsrud, Helene; Therrien, Marc
Abstract: The Ras/MAPK-signaling pathway plays pivotal roles during development of metazoans by controlling cell proliferation and cell differentiation elicited, in several instances, by receptor tyrosine kinases (RTKs). While the internal mechanism of RTK-driven Ras/MAPK signaling is well understood, far less is known regarding its interplay with other corequired signaling events involved in developmental decisions. In a genetic screen designed to identify new regulators of RTK/Ras/MAPK signaling during Drosophila eye development, we identified the small GTPase Rap1, PDZ-GEF, and Canoe as components contributing to Ras/MAPK-mediated R7 cell differentiation. Rap1 signaling has recently been found to participate in assembling cadherin-based adherens junctions in various fly epithelial tissues. Here, we show that Rap1 activity is required for the integrity of the apical domains of developing photoreceptor cells and that reduced Rap1 signaling hampers the apical accumulation of the Sevenless RTK in presumptive R7 cells. It thus appears that, in addition to its role in cell–cell adhesion, Rap1 signaling controls the partitioning of the epithelial cell membrane, which in turn influences signaling events that rely on apico-basal cell polarity.